The impact of digital technologies on modern society. An example of a social credit rating system in China - A. P. Klimovich (Цифровая социология)
The issue on the first principles of Internet building in China has been considered. An overview of establishment has been made and the specifics of the development of the Chinese information technology industry in recent years has been analysed. The influence of the state policy on digital technology market has been studied. The principles of Chinese authorities’ actions in relation to the domestic and foreign high tech markets have been highlighted. The causes of the Chinese industry rapid development, based on the state activity aimed at supporting the local manufacturers, have been analysed. Protectionism policy defining the government control pattern has been evaluated. Chinese development main program scale, embracing not only national, but also world economics, has been considered. It has been shown how domestic economy policy coincides with Chinese government foreign policy and how it is directly reflected in it. A parallel has been drawn between the principle of establishing of social credit system and the idea of counting merits and drawbacks, laying in the basis of finely built system of rewards and punishments of traditional Chinese society. A connection of this tradition with the official goal of the system, stated by the government of China to teach the Chinese society to become more honest by complete surveillance over people, has been shown. It has been shown how this system classifies people into several categories, creating the lists of those to reward and those to censure. The mechanism of how the state uses private companies’ resources, applying all its power to influence on them, has been considered. A critical analysis of the foundations of the system from the point of view of Western democracy values has been carried out. An overview of development prospects of the studied system and the assessment of the risks associated with it have been made. It has been noted that despite the fact that the basic ideas for the system are borrowed from the international practice of the financial sector, making decisions on authorizing going beyond the judicial system and transferring the classification of people in the lists of good and bad to the level of algorithms run counter to the principles of European and international law.